The Relationship Between Dietary Compliance and Quality of Life Among Patients with Chronic Kidney Disease Undergoing Hemodialysis at Kertosono Regional Hospital - Sony Wahyu Tri Cahyono (Journal for Quality in Public Health, 2026)
Patients who have been diagnosed with kidney failure must undergo hemodialysis routinely throughout their lives obediently which has an impact on the patient's quality of life. In patients with CKD, it is often recommended to regulate their diet in order to support improving their quality of life. The purpose of this study was to determine the relationship between dietary compliance and the quality of life of CKD patients undergoing hemodialysis therapy in the Hemodialysis Room of RSD Kertosono. The design in the correlation study with a cross-sectional approach. Technique sampling use Purposive Sampling and a sample 35 patients with CKD undergoing hemodialysis. Measurement of the independent variable, namely dietary compliance with a questionnaire and the dependent variable, namely quality of life with the WHOQoL-BREF questionnaire. Statistical tests using spearman rank (α = 0.05). The results of this study found that most of the dietary compliance was in the non-compliant category, as many as 21 respondents (60%) and almost half of the quality of life was in the poor quality of life category, as many as 17 respondents (49%). The results of the Spearman rank statistical test obtained ρ value = 0.000 ≤ α (0.05) r = 0,775 a strong positive correlation so that H1 was accepted, which means that there is a relationship between dietary compliance and the quality of life of chronic kidney failure patients undergoing hemodialysis therapy in the Hemodialysis Room of RSD Kertosono. Dietary compliance greatly affects the quality of life in CKD patients undergoing hemodialysis.